EVALUATION OF HEAD LOSSES IN FLUID TRANSPORTATION NETWORKS (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
Energy losses in pipes used for the transportation of fluids (water, petroleum, gas,etc.) are essentially due to friction, as well as to the diverse singularities encountered. These losses are usually converted into head reductions in the direction of the flow. The knowledge of data of such transformation allows the determination of the necessary power needed for the transportation of the fluid between two points. It constitutes the necessary calculation basis necessaryfor the design and analysis of transport and distribution networks. The review of the different relationships allowing the determination of these losses and their comparison to the experimental results obtained by the authors, constitute the object of this study.